Novel Association of RAD54L Mutation with Müllerian Clear Cell Carcinoma of the Male Urethra: New Insights Regarding the Molecular Mechanisms of a Rare Tumour - Deng, Huiyan; Ding, Yan; Wang, Zhiyu; Liang, Xiangdong; Liu, Yueping (Current Cancer Drug Targets, 2024)
Introduction: Müllerian clear cell carcinoma of the male urethra is similar to that of the female genital tract in terms of morphology and immunohistochemical expression but is rarely observed in clinical practice. Case Presentation: Here, we report the case of a 65-year-old man diagnosed with Müllerian clear cell carcinoma who harboured a mutation in RAD54L. This patient was diagnosed by electrocautery and ultimately underwent prostatectomy. After a six-month follow-up period, no signs of recurrence or additional malignancy were found. Based on our analysis of the available literature, it appears that Müllerian clear cell carcinoma with RAD54L mutation has not been reported until now. Conclusion: This case enhances our knowledge of the molecular biology of Müllerian clear cell carcinoma of the male urethra, which will help clinicians select optimal treatment options for this rare cancer in patients with specific driver mutations.
Keywords: next-generation sequencing